(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article is a reflection about Turkish Shadow Theatre, Karagöz Theatre. It presents Karagöz techniques; the structure of Karagöz plays and the main characters, providing the reader with a clear view of Karagöz Shadow Theatre, an art form that will complete its 500th birthday in 2017. Keywords: Turkish shadow theatre. Karagöz theatre. Theatre History.